2017
DOI: 10.3390/molecules22040660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tanshinone IIA Developmental Toxicity in Zebrafish Embryos

Abstract: Tanshinone IIA (Tan-IIA) is derived from the dried roots of Salvia miltiorrhiza Bunge, a traditional Chinese medicine. Although Salvia miltiorrhiza has been applied for many years, the toxicity of the mono-constituent of Salvia miltiorrhiza, tanshinone IIA, is still understudied. This study evaluated the cardiotoxicity and developmental malformations of Tan-IIA by using zebrafish normal embryos and dechorionated embryos. After treatment with Tan-IIA in different concentrations for four-day periods, obvious per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…Although tan IIA had a positive effect at the doses used here, we and other groups found that tan IIA increased the cytotoxicity of cortical neurons and SH-SY5Y cells at higher doses [22,25,57]. Furthermore, tan IIA exhibited severe cardiotoxicity, development malformation, and growth inhibition at high concentrations in a zebrafish embryo model [58]. These studies demonstrate that tan IIA has cytotoxic effects at higher doses and point to the potential risk of clinical application of increased doses.…”
Section: Discussioncontrasting
confidence: 39%
“…Although tan IIA had a positive effect at the doses used here, we and other groups found that tan IIA increased the cytotoxicity of cortical neurons and SH-SY5Y cells at higher doses [22,25,57]. Furthermore, tan IIA exhibited severe cardiotoxicity, development malformation, and growth inhibition at high concentrations in a zebrafish embryo model [58]. These studies demonstrate that tan IIA has cytotoxic effects at higher doses and point to the potential risk of clinical application of increased doses.…”
Section: Discussioncontrasting
confidence: 39%
“…Teratogenic effects such as scoliosis, malformation of the tail, and pericardium oedema of dechorionated embryos were manifested at a concentration of about 1 μ M. Normal embryos were less sensitive to Tan-IIA, but with the increasing concentration, severe abnormalities of heart and pericardium were observed. Moreover, after treatment with Tan-IIA ≥ 6 μ M, the time it took for the embryos to mature into fish was longer than that for the control [43].…”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrated that treatment with a high dose of tan IIA alone increased the cytotoxicity of cortical neurons and SH-SY5Y cells, suggesting that tan IIA has a positive effect on cell viability at low dose [30,39,40]. Furthermore, tan IIA exhibited severe growth inhibition, development malformation, and cardiotoxicity at high concentrations in a zebrafish embryo model, pointing to the potential risk of clinical application of increased doses [41]. These researches showed that tan IIA has cytotoxic effects at higher doses itself.…”
Section: Discussionmentioning
confidence: 99%